Tingkat Stres Dan Perawatan Diri (Self-Care) Pada Klien Diabetes Melitus Tipe 2 Di Poli Penyakit Dalam BLUD RSUD Dr. Doris Sylvanus: Level Of Stress And Self-Care In Clients Of Diabetes Melitus Type 2 In Poly Disease In BLUD RSUD dr. Doris Sylvanus - Natalansyah, Natalansyah; Wulandari, Wulandari; Mansyah, Barto (Jurnal Surya Medika (JSM), 2020)
The International Diabetes Federation (IDF) estimates the number of DM increases in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. Type 2 diabetes is the most common type. Diabetes is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, insulin action, or a combination. Diabetes mellitus can cause clinical changes in diabetics. The purpose of this study was to study the relationship of stress levels with self-care on type 2 DM clients in BLUD Internal Medicine dr. Doris Sylvanus. This research method uses a cross-sectional study design, with a purposive sampling technique, the number of samples in this study were 35 respondents, collecting data using a Diabetes Self-Care Activity Summary questionnaire (SDSCA and Diabetes Disorders Scale (DSS) and analyzed using the chi-square test The results of this study indicate that of the 20 respondents who were severely stressed 18 respondents were not good in self-care and of the 15 respondents who increased mild stress 10 respondents were able to perform self-care well. = 0.001, where the p-value <α (α = 0 05) It can be concluded that there is a significant relationship between stress levels and self-care where the higher the stress level, the lower the self-care treatment.